Strengthening Local Food Systems: The Impact of Farmer Groups on Rice Production in Kaloling Village, Indonesia - Winadia; Ahfandi Ahmad; Fadilah Nurdin; Putra Astaman; Sadam Suliman Mohamed Yousof (Sustainable Agribusiness Review, 2025)
Farmer groups have not yet played an optimal role, as evidenced by groups whose members are less active, groups that have difficulty retaining members, while some farmer groups are actually progressing, and many members only use the group to obtain subsidized fertilizer and plant seeds. This study aims to determine the role of farmer groups in increasing rice production in Kaloling Village, East Sinjai District, Sinjai Regency. The research method used is a quantitative descriptive method. Sampling was conducted using simple random sampling with 80 respondents. The analysis revealed that the role of farmers' groups as learning classes and production units does not have a significant impact on rice production in Kaloling Village. This is attributed to low levels of farmer education, inappropriate learning methods, and farmers' tendency to farm individually. On the other hand, the role of farmer groups as a vehicle for cooperation among group members does influence rice production. The cooperation established creates a collaborative environment that encourages farmers to increase rice production.